GUide sheath Advancement and aspiRation in the Distal petrocavernous internal carotid artery (GUARD) Technique during Thrombectomy Improves Reperfusion and Clinical Outcomes - Ansari, S.A. (AJNR Am J Neuroradiol, 2019)
BACKGROUND AND PURPOSE: Adjunctive techniques to stent retriever thrombectomy include balloon-guide catheters and/or distal access catheters for aspiration. We describe a novel technique using a flexible, 6 French 088 distal guide sheath advanced past the skull base to augment mechanical thrombectomy. We studied the relative safety and efficacy of this technique in the setting of a combined stent retriever–distal access catheter aspiration thrombectomy protocol. MATERIALS AND METHODS: We performed a retrospective case-control study of intracranial internal carotid artery or M1–M2 middle cerebral artery occlusions requiring mechanical thrombectomy. Patients were divided into 2 groups based on thrombectomy techniques: conventional stent retriever with distal access catheter aspiration without (standard) and with adjunctive GUide sheath Advancement and aspiRation in the Distal petrocavernous internal carotid artery (GUARD). Using propensity score matching, we compared procedural safety, reperfusion efficacy using the modified Thrombolysis in Cerebral Infarction scale and clinical outcomes with the modified Rankin Scale. RESULTS: In comparing the GUARD (45 patients) versus standard (45 matched case controls) groups, there were no significant differences in demographics, NIHSS presentations, IV rtPA use, median onset-to-groin puncture times, procedural complications, symptomatic intracranial hemorrhage, or mortality. The GUARD group demonstrated significantly higher successful mTICI ≥2b reperfusion rates (98% versus 80%, P = .015) and improved functional mRS ≤2 outcomes (67% versus 43%, P = .04), with independent effects of the GUARD technique confirmed in a multivariable logistic regression model. CONCLUSIONS: The GUARD technique during mechanical thrombectomy with combined stent retrieval–distal access catheter aspiration is safe and effective in improving reperfusion and clinical outcomes.